Differences in Physical and Psychological Parameters in Sub-Elite, Male, Youth Soccer Players with Jumper's Knee Following Physical Therapy Compared to Healthy Controls: A Longitudinal Examination - Marc Niering; Thomas Muehlbauer (International Journal of Sports Physical Therapy)
# Purpose/Background Many adolescent athletes suffer from jumper's knee (JK) over a long period of time and return to sports before symptoms are fully resolved. Current treatment methods may not reduce pain in the short term, especially not during a competitive season. The purpose of this study was to investigate differences in physical, psychological, and injury-/pain-related parameters in sub-elite male youth soccer players, who previously underwent physical therapy for JK compared to healthy controls (HC) over the course of a season.